Non-Conformist Heroine: The Assertive Female in Alobwed ‘Epie’s The Lady With A Beard - Lum, Mary Louisa (Richtmann Publishing, 2011)
Postcolonial discourse has, for the past decade, been a major area of focus for scholarship in the academia. The issues ofalterity, identity, subeltanism, violation, religion, and culture which find expression in post-colonial studies has been debated from multipleperspective by scholars representing different and varied interests. This suggest therefore that within the framework of Postcolonial studiesthe creation of meaning goes along with a vision that maintains that postcolonial societies are caught in complex situations that resist anysingle interpretation. These complexities are experienced both at the individual and the societal levels. The expectations, roles and theissues attached to gender; the assumptions, the constraints, and the benefits of defined gender binarism in postcolonial societies createavenues for the interpretation and the creation of meaning in a postcolonial text. The Lady With A Beard by Cameroonian novelist andscholar, Alowbwed ‘Epie, is one of such postcolonial texts that open-up new avenues of discourse on the question gender.